Editorial for applied econometrics - Chia-Lin Chang (Journal of Risk and Financial Management, 2020)
This Editorial evaluates 14 invaluable and interesting articles in the Special Issue "Applied Econometrics" for the Journal of Risk and Financial Management (JRFM). The topics covered include recovering historical inflation data from postage stamps prices, FHA loans in foreclosure proceedings through distinguishing sources of interdependence in competing risks, information in earnings forecasts, nonlinear time series modeling, a systemic approach to management control through determining factors, economic freedom and FDI versus economic growth, efficient cash use of the Taiwan dollar, financial health prediction in companies from post-Communist countries, influence of misery index on U.S. Presidential political elections, multivariate student versus Gaussian regression models in finance, financial derivatives markets and economic development, income inequality and economic growth in middle-income countries, abnormal returns, mis-measured risk, network effects, and risk spillovers in stock returns.
Keywords: 330; economic growth; abnormal returns; FDI; FHA loans; financial derivatives markets; historical postage stamps prices; income inequality; mis-measured risk; network effects; risk spillovers; U.S. Presidential political elections